Living with the Internet and online dangers - Sandler, Corey (New York Facts On File, 2010)
The Internet is filled with online dangers - from those who want to infect computers with destructive viruses to criminals who want to steal money, ruin reputations, or cause personal harm. This book highlights the risks and problems that come with modern Web technology, as well as what teens can do to protect themselves.
Is cyberspace bad for you? -- Your online social life -- Shopping without dropping -- Online job hunting -- File-sharing : free and frightful -- E-mail scams and Internet fraud -- Internet drugstores -- Finding that special someone -- Maintaining your identity -- Viruses : a computer can develop a cold -- Don't click on that link -- Cell phones, IMs, and text messaging -- Wireless security -- How to help friends cope with internet and online dangers.
95732
Keywords: Internet and teenagers; Internet -- Safety measures; Computer security